Diffusion tensor imaging – Magnetic resonance tractography in stroke patients to predict clinical outcome - P Hemachandra; K Ravi; M R Srinivas (Journal of the Indian Academy of Geriatrics, 2023)
Background: The challenge for neuroscience in patients with stroke is to provide an accurate prediction of functional impairment poststroke, to aid therapy and help early recovery. The sensitivity of diffusion tensor imaging (DTI) metrics to predict the clinical outcome using the modified Rankin Scale and Barthel score in early stroke was the objective of the study. Materials and Methods: A prospective observational study was conducted between October 2019 and October 2021 involving 86 patients with stroke. DTI sequences were taken on day 2–day 10 after the stroke. The National Institutes of Health Stroke Scale (NIHSS) was obtained at the time of the scan. The modified Rankin Score (MRS) and Barthel index scoring were used to do the clinical assessment and were done on day 7, day 30, and day 90. Results: There was a weak positive correlation between the NIHSS and Fractional Anisotropy (FA) and the NIHSS and axial diffusivity curve. There was a strong positive correlation between the NIHSS and voxels (infarct), and this correlation was statistically significant (rho = 0.75 and P ≤ 0.001. There was a weak positive correlation between the relative Average Diffusion Coefficient (rADC) and MRS of day 7, day 30, and day 90. There was a strong positive correlation between the voxels and NIHSS, and this correlation was statistically significant (rho = 0.75 and P ≤ 0.001). Conclusions: The NIHSS is a well-known clinical indicator to classify the severity of stroke. DTI metrics – FA and relative Fractional Anisotropy (rFA) are surrogate markers to predict the long-term motor outcome in stroke patients.